2009
DOI: 10.1152/ajprenal.90718.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional TRP and ASIC-like channels in cultured urothelial cells from the rat

Abstract: Transient receptor potential (TRP) and acid-sensing ion channels (ASIC) are molecular detectors of chemical, mechanical, thermal, and nociceptive stimuli in sensory neurons. They have been identified in the urothelium, a tissue considered part of bladder sensory pathways, where they might play a role in bladder function. This study investigated functional properties of TRP and ASIC channels in cultured urothelial cells from the rat using patch-clamp and fura 2 Ca 2ϩ imaging techniques. The TRPV4 agonist 4␣-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 58 publications
10
81
0
Order By: Relevance
“…TRPV4 was initially described in the urothelium of rodents and humans (146). Coexpression of the two receptors was observed in 20% of rat urothelial cells (167). TRPV4 may also be expressed in bladder afferents; ϳ30% of L6 dorsal root ganglia neurons that project to the urinary bladder coexpressed TRPV1 and TRPV4 (57,66).…”
Section: Trp Channel Antagonistsmentioning
confidence: 99%
“…TRPV4 was initially described in the urothelium of rodents and humans (146). Coexpression of the two receptors was observed in 20% of rat urothelial cells (167). TRPV4 may also be expressed in bladder afferents; ϳ30% of L6 dorsal root ganglia neurons that project to the urinary bladder coexpressed TRPV1 and TRPV4 (57,66).…”
Section: Trp Channel Antagonistsmentioning
confidence: 99%
“…However, presence of active potassium channels, including Kir2.1 and BK, have been detected in cultured human bladder urothelial cells, with altered function of these channels in interstitial cystitis and overactive bladder [15,16]. The conductance of Kir2.1 is small (~27 pS) [15], whereas conductance of BK is large (~180 pS) [16], so the 22 pS potassium current detected in this study might be Kir2.1. It should be noted that these channel activities in the prior urothelial studies were measured in cultured monolayer of cells from human subjects.…”
Section: Measurement Of Urothelial Cell Function In Situmentioning
confidence: 52%
“…Also, different mechanisms of apoptotic cell removal from the tissue have been described: the cells can be exfoliated into the lumen of an organ; they can be phagocytosed and digested, mostly by macrophages, or even by adjacent cells in tumours [23][24][25][26]. Moreover, Kullmann et al [27] showed that stimulation of different receptors (TRPV1, TRPV4, TRPM8, TRPA1, and ASIC-like channels) in primary urothelial cell culture induces ionic currents and changes in intracellular calcium concentration. It was postulated that TRP channels might be involved in the mechanisms underlying the release of transmitters from the urothelium and might contribute to the putative sensory function of the urothelium, as well as playing a role in homeostatic mechanisms related to cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%